Utilizing Instagram Social Media for Photo Corner Promotional Services in Surabaya - Iswanto, Rendy; Saniscara, Pramesti (Universitas Ciputra, 2017)
The Creative Industries potential has grown along with the development of Visual Communication Design science as well as the technology development. Photo corner service is one type of business that was born from the Visual Communication Design and technology development. However, the photo corner bussiness in Surabaya has a high level of competition so that the photo corner bussiness owner must have special way in promotion in order to be able to compete with its competitors. Social media is one of the promotional media that is currently becoming a trend. The benefits of social media for this promotion are interesting to investigate due to the high number of social media usage these days. Through this research is expected to know the benefits of social media for promotion, especially on photo corner service business.